Molecular and pathological identification of ovine pulmonary adenomatosis at Mosul city abattoirs - Osama Z. Jiad; Ahmed M. Al-Saidya (Iraqi Journal of Veterinary Sciences)
Ovine Pulmonary adenomatosis OPA is a frequent condition that affects small ruminants, characterized by inflammation of the lung parenchyma, and causes polyp-like hyperplasia of the epithelium lining the alveoli and interstitial tissue like bronchi. It is frequently brought on by the Jaagsiekte virus. Samples from sheep animals at Mosul's slaughterhouse and butcher shops were collected. The RT-PCR results consider the first molecular identification of the JSRV virus in Mosul city. The Macroscopic examination revealed gray-colored tumor nodules scattered across the surfaces of the lung lobes. The tumor tissue had clear and distinct boundaries from the adjacent pink pneumatic lung. Histological analysis showed nodular tumor areas (proliferative pulmonary nodules) were composed of carcinomatous cells supplementary with an adequate amount of extracellular matrix, characteristic columnar and cuboidal metaplasia, as well as hyperplasia of pulmonary cells, especially the pneumocytes (type II), an epithelial cell (secretory types) in the pulmonary alveoli, Non-ciliated Clara cells as well as the epithelial lining of the terminal bronchioles. Finally, our study sheds light and provides data on the importance of OPA in Mosul abattoir through the PCR diagnosis of the causative agent, and the macroscopic and histological pathological changes.